Communication strategy of the tourism department in promoting tourism air putri waiyoho in Kawa village - Kissya, Vransisca; Rado, Yunita Andora (Universitas Wiralodra, 2023)
Indonesia has the potential and attractiveness in the field of tourism, especially biodiversity natural tourism which optimally needs to be further developed for the welfare of the community. This research is a qualitative descriptive study that aims to find out how the Promotional Communication Strategy of the West Seram Regency Tourism Office in Promoting Putri Waiyoho Water Tourism in Kawa Village. Data collection techniques used in the form of observation, interviews and documentation. In addition, the data analysis technique was carried out based on three streams of activities simultaneously, namely data reduction, data presentation and drawing conclusions on the research results. In accordance with the initial objective of the research, namely to analyze the promotional communication strategy used by the West Seram Regency Tourism Office in increasing tourist visits, an effective promotional communication strategy is one of the techniques carried out to break through consumer tastes and desires, creating an image that is able to influence a number of people who are expected to have attention to the product or service offered. The promotional communication strategy for the West Seram Regency Tourism Office, namely, (1) Selection of Communicators: used by the West Seram Regency Tourism Office in Promoting Air Putri Waiyoho Tourism is by placing communicators who have credibility and knowledge about Air Putri Waiyoho tourism as a whole, ( 2) Message Design: The Tourism Office in designing messages is the use of sentences based on the beauty of each tourist object in each region, and Media Selection: the media used is based on the availability of funds. Print media such as brochures, templates while for online media, namely websites and social media. Attending events is also done by watching documentary videos about tourist attractions.